Raman Spectroscopy Of Fullerene-Like Molecules Of Silicon Dioxide (SiO2)N(H2O)N/2 - Filonenko, O.V. (Physics and Chemistry of Solid State, 2016)
The Raman spectra of monosilicic, disilicic acid molecules, tetra- and pentasilicic acid molecules with cyclic structure, cage-like okta- and dekasilicic asid molecules, and of fullerene-like molecule (SiO2)N(H2O)N/2 have been calculated using density functional theory method (exchange-correlation functional B3LYP and basis set 6-31G (d, p)) and assignment of frequencies in conformity with the shape fluctuations have been executed.